2018
DOI: 10.1111/aec.12592
|View full text |Cite
|
Sign up to set email alerts
|

The role of frugivorous birds in fruit removal and seed germination of the invasive alien Cotoneaster franchetii in central Argentina

Abstract: Many invasive plant species have fleshy fruits that are eaten by native frugivorous birds which disperse their seeds and may facilitate their germination, playing an important role in plant invasion success. The fleshy-fruited shrub Cotoneaster franchetii (Rosaceae) is an important invasive alien in the mountainous regions of central Argentina. To determine the role of avian frugivorous in fruit removal of this species, we conducted a frugivore exclusion experiment including bagged and unbagged branches in 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
2
9
0
1
Order By: Relevance
“…From our observations and remote camera-trap data, results support that birds are important potential seed dispersers (Díaz Vélez et al 2018, Vergara-Tabares et al 2018). This showed that bird species are effective seed dispersers of P. angustifolia.…”
Section: Discussionsupporting
confidence: 67%
“…From our observations and remote camera-trap data, results support that birds are important potential seed dispersers (Díaz Vélez et al 2018, Vergara-Tabares et al 2018). This showed that bird species are effective seed dispersers of P. angustifolia.…”
Section: Discussionsupporting
confidence: 67%
“…Seed abrasions and scarification by birds increase seed coat permeability and thus, quick imbibition (Figueroa and Castro, 2002); this may also explain the surprising observation of both the highest and accelerated seed germination of O. robusta after treatment by the smaller birds. When matched with conducive conditions, accelerated seed germination is important for reducing competition with siblings for resources, avoiding secondary predators (Diaz-Velez et al, 2018), and promoting plant species colonisation and invasion success. This finding points to different bird species having different impacts on seeds of similar plant species, as demonstrated in seeds of Acacia cyclops consumed by different dove species (Mokotjomela et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Endozoochory is a common seed dispersal strategy involving the production of fruits to attract frugivores that feed on the fruits and disperse seeds in their droppings 3 . Beside dispersal, endozoochory enhances germination by separating seeds from the pulp (often containing germination inhibitors), fertilizing the ground with fecal material, and scarification of the seed coat 4 7 . Interaction between plants and frugivores is assumed mutualistic, with the consumer benefiting from nutrients in fruits and the plant benefiting from seed dispersal 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%